Novel numerical method for the analysis of semi-rigid jointed lattice shell structures considering plasticity. (December 2017) - Zhao, Zhongwei; Liu, Haiqing; Liang, Bing
Highlights: A novel numerical method that can consider joint bending stiffness and axial stiffness has been proposed. Both of the plasticity and semirigid joint can be taken into account. Influence of joint bending stiffness and axial stiffness on the behaviour of latticed shell structures were studied. The joint bending stiffness has great influence on buckling load capacity of latticed shell structures. The joint axial stiffness has different influence on different kinds of structures. Abstract: The joint bending and axial stiffness significantly influence the mechanical performance of lattice shell structures. However, most finite element models of the actual project established in the general finite element software are rigid or hinge-connected for simplicity. These characteristics are inconsistent with the actual situation and may lead to a large error. A novel numerical method was proposed in this paper to estimate the influence of joint stiffness, which includes bending and axial stiffness, on the mechanical behavior of lattice shell structures. This method can be used for inelastic analysis. First, the accuracy of the proposed element model was validated. The model was used to analyze lattice shell structures. The proposed element model can simultaneously consider semi-rigid joints and inelasticity with high accuracy, and it can be conveniently constructed in general finite element software.